PROGRAM PENDAMPINGAN USAHA TANI PADI RAMAH LINGKUNGAN PADA GAPOKTAN HARAPAN DI DESA IDA MANGGALA, KECAMATAN SUNGAI RAYA, KABUPATEN HULU SUNGAI SELATAN - Riza Adrianoor Saputra; Noorkomala Sari; Akhmad Rizali; Faridawati Junjung Nindhiani; Indriani; Ria Anita Pertiwi; Joni Yogo Prayogo; Henny Ramelan Saputri (Jurnal Abdi Insani, 2026)
Sungai Raya is one of the sub-districts in South Hulu Sungai Regency (HSS) with extensive potential for rice fields. Ida Manggala is one of the villages in Sungai Raya District with significant potential for its rice commodity. Some farmers from the Harapan Farmers Group (Gapoktan) have implemented rice cultivation using an eco-friendly concept without synthetic fertilizers and chemical pesticides. However, the application of the eco-friendly farming concept is still limited to the use of fertilizers and pesticides only. The purpose of this activity is to increase the knowledge and skills of farmers in Ida Manggala Village, Sungai Raya District, Hulu Sungai Selatan Regency in making liquid organic fertilizer (LOF) and botanical pesticides as an effort to implement the concept of eco-friendly rice cultivation. This activity is carried out thru socialization, technical training, and hands-on practice in making liquid organic fertilizer (LOF) and botanical pesticides. This activity was attended by 30 participants, consisting of rice farmers who are members of the Harapan Farmers Group Association. The service activity went well, with participants enthusiastically and actively participating in the training, enabling farmers to practice making liquid organic fertilizer (LOF) and botanical pesticides. The conclusion drawn is that this activity can increase the knowledge and skills of farmers in Ida Manggala Village, Sungai Raya District, Hulu Sungai Selatan Regency. After the activity, almost all participants understood the benefits, functions, and how to make Liquid Organic Fertilizer (LOF) and botanical pesticides, and were able to apply them to their rice cultivation land.